PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SEKTOR FOOD & BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Wulandari, Yanna; Maqsudi, Achmad (JEA17: Jurnal Ekonomi Akuntansi, 2019)
ABSTRACTThis study aims to examine and analyze the effect of company size, leverage and sales growth on tax avoidance with profitability as an intervening variable in the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This type of research is quantitative research with a descriptive approach. The data used are secondary data in the form of company financial statements obtained from the IDX website. The sample studied was 6 food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period using purposive sampling techniques. Data analysis techniques in this study used PLS (Partial Least Square) 3.0 software. The results of this study indicate that company size, leverage, and sales growth have no significant effect on profitability and tax avoidance. But profitability as an intervening variable has a significant effect on tax avoidance.Keywords: Company Size, Leverage, Sales Growth, Profitability, Tax Avoidance